Glottopolitical Interventions and Virtuality in Spanish Language Teaching for Senegalese Immigrants during the Pandemic (Buenos Aires, 2020–2021) - Murguia Cruz, Nelida Abril (2023)
This paper is the result of an ongoing research on glottopolitical interventions carried by a group of instructors working in educational spaces, both popular and institutional, teaching Spanish to Senegalese immigrants in Buenos Aires. Being one of the researchers in charge of the study, I will present on this occasion an article focused on two courses: a Spanish course offered by BTM / Bloque de Trabajadorxs Migrantes (Block of Immigrant Workers), held on the YouTube channel Damay Jaangë Español, and a course conducted with the help of the professorship in Grammar “C” at the Faculty of Philosophy and Letters of the Universidad de Buenos Aires (UBA), which was part of a textile production project in charge of Fundación Nobleza Obliga (Nobleza Obliga Foundation).Multiple restrictive measures have been decreed in Argentina since March 2020 in order to contain the outbreak and minimize the spread of the COVID-19 virus. One of such measures was the suspension of face-to-face classes in all the educational levels and the consequent use of digital platforms to support the teaching process. In the case of immigrant Senegalese students, some of the educational approaches involved the implementation of virtual teaching modes on video conferencing platforms or social media.The data for this research come from an ethnographic (Cassels/Ricento 2013) and discursive (Arnoux 2012) approach within the Spanish teaching spaces. In the case of BTM, I am a member of the Spanish commission and I participate in the production of Damay Jaangë Español. As for the textile project, I collaborated with the implementation of the course, being an intermediary between the professorship and the organizers of the course, and interviewing the Senegalese participants of the project.This research is set in the framework of Glottopolitics (Arnoux 2012; Del Valle 2007), understood as an inter-disciplinary perspective within language studies, which implies questioning the subject of study both in its linguistic and socio-political dimensions, in order to understand it and explain it. Glottopolitics primarily explores interventions in the public space of language, linguistic ideologies and its relation and effect in power structures and social relations.I will present hereafter a sociolinguistic description of Senegalese migration, considering its transnationality. Then, I will examine some of its glottopolitical strategies and its relation with Information and Communications Tecnhologies (ICTs). In the second section, I will describe the Spanish courses as glottopolitical interventions, contemplating their context of emergence and their relation with popular education. Finally, I will describe the project by BTM Damay Jaangë Español and the Spanish course imparted via WhatsApp for the textile project, and then I will look into the contents of both courses and the way ITCs and virtuality are implemented in each of them.